Quality Assessment of DJI Zenmuse L1 and P1 LiDAR and Photogrammetric Systems: Metric and Statistics Analysis with the Integration of Trimble SX10 Data - Filippo Diara; Marco Roggero (Geomatics, 2022)
This manuscript focuses on a quality assessment of DJI’s new sensors: the Zenmuse L1 and P1, which are LiDAR and photographic payload sensors, respectively, for UAVs/UASs. In particular, metric and statistical analyses aim to evaluate the data obtained from different 3D survey instruments. Furthermore, we compared these sensors with TLS data derived from a Trimble SX10 scanning station. The integration of LiDAR and photogrammetric data was then performed and tested inside a complex architectural context, the medieval Frinco Castle (AT-Italy). Point clouds obtained from aerial and terrestrial instruments were analysed and compared using specific tools to calculate variance/distance between points and cloud alignment (via the ICP algorithm), as well as to perform qualitative estimations (especially roughness analysis). The medieval castle proved crucial for the purpose of analysing different metric data of an extremely complex architecture and achieving more accurate results. The collected dataset and performed analyses are now essential information for the consolidation and restoration programme.